The long march through the institutions: Emerging powers and the staffing of international organizations - Michal Parizek; Matthew D. Stephen (Cooperation and Conflict, 2021)
How successful have emerging powers been at increasing their representation within the secretariats of international organizations (IOs)? We examine the representation of the BRIC countries (Brazil, Russia, India, and China) in the International Monetary Fund (IMF), the World Trade Organization (WTO) and the United Nations (UN) System, including the UN Secretariat, over the last two decades. The analysis reveals four major findings. First, some redistribution of staff positions from established to emerging powers has taken place, but it has been relatively minor. Second, nationals from emerging powers are still strongly under-represented in international secretariats in comparison with those from established powers. Third, emerging powers' representation at the IMF and WTO increased more than in the UN, where it actually declined. Fourth, there is strong variation between emerging powers: India appears to be the most successful emerging power in sending its nationals to the secretariats of IOs, Brazil's and China's records are mixed, and Russia has fared poorly. We interpret our findings in light of international relations theories and theories of institutional path dependence. The results suggest that staffing patterns are only loosely related to shifts in economic size and are subject to strong independent institutional dynamics.
Keywords: 300; emerging powers; international organizations; path dependency; secretariats; staff